PEMBUATAN CIWEED (CILOK-SEAWEED) SEBAGAI ALTERNATIF PANGAN SEHAT DAN BERGIZI - Rizka Rian Fauziah; Novita Santi Lovabyta; Wulan Suci Wahyuningtyas (Faculty of Agricultural Technology, University of Jember, 2016)
Cilok is one of local food from West Java which is favoured by all community. Originally, cilok made from “aci” (tapioca starch), meat, and spices. The proportion of “aci” is greater than meat, usualycilok production use 10% of meat by raw material. Problem that usually found in cilok manufacturing in Indonesia is the used of non-permitted food additive, such as borax. The use of borax in cilok manufacture is to improve the texture (chewy) and as preservative. Cilokconsumers generally prefercilok that has a chewy texture. One alternative that can be used to improve the chewy texture oncilok is the use of seaweed. The addition seaweed on cilok manufacturing also improves nutrition and functional properties of cilok. In this research, the cilok that produce by additiof of seaweed we call “ciweed”. The results of the proximate analysis on ciweed showed that moisture, ash, fat, proteinand carbohydrate content respectively by 55.76%; 2.3%; 0.24%; 3.33% and 38.37%. In 100 gof Ciweedcontain energy as much as 306.7 kcal. Based on the economic analysis, ciweed manufacture is highly prospective for further development into a business because the B/C ratio is 1, 56. Keywords: cilok, ciweed, seaweed,healthy and nutrious food